Analisis Manfaat Media Audio Visual Animasi sebagai Bahan Pembelajaran Efektif untuk Anak Sekolah Dasar - Fatimatus Zahroh; Astri Apriyani; Yusi Afrilia (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This article analyzes the benefits of animated audio-visual media as an effective learning tool for elementary school students. The use of animated videos has been proven to increase student participation and learning outcomes, and is more effective than conventional presentation videos in improving concentration. Animated media presents complex concepts in an interesting and easy-to-understand way, in line with constructivist learning theory. The research method used is a literature study with a qualitative approach, collecting data from various sources such as journals and relevant articles. The results of the study show that animated media can explain material visually, increase motivation, and clarify the relationship between concepts. However, challenges such as high production costs, long processing times, and limited devices and teacher capabilities are obstacles that need to be overcome to maximize the use of this media in learning.